'Expecting': occupant model incorporating anthropometric details of pregnant women. (24th August 2009) - Acar, B. Serpil; Weekes, Alix; Van Lopik, David
This study reports the research for a design tool related to pregnant women's safety during car travel. Anthropometric measurements are taken to generate an occupant model incorporating pregnancy related changes. These anthropometric changes mean that a pregnant occupant may be excluded by the designs, based upon non-pregnant female anthropometry. The paper explains the generation of a comprehensive parametric computer aided model of a pregnant occupant, 'Expecting'. The model can represent different size pregnant occupants as well as the size differences occurring in standing and seated postures. This model can be used as a design tool for automotive designers to help ensure that vehicle designs can accommodate the anthropometric needs of pregnant occupants.